Capacity Building Institutional Department of Women's Empowerment, Child Protection, Population Control and Family Planning, Bintan Regency - Defitriyani Defitriyani; Rumzi Samin; Edy Akhyari (Journal of Governance and Public Policy, 2022)
Capacity Building as a form of institutional progress for the creation of better organizational performance in perfecting the implementation of the bureaucracy during the COVID-19 pandemic. The purpose of this study is to analyze capacity building in the Department of Women's Empowerment, Child Protection, Population Control and Family Planning, Bintan Regency. The research method used a qualitative approach by reviewing secondary data in the 2020 Government Agency Performance Accountability Report (LAKIP) and other documents which were then analyzed in-depth using the concept of institutional capacity building as a form of evaluating organizational performance in the future in reform bureaucracy. The results show that institutional capacity building in the Department of Women's Empowerment, Child Protection, Population Control, and Family Planning in Bintan Regency has to support and inhibiting factors during the COVID-19 pandemic. it focuses on regulations and rules during a world health emergency that makes the government system not in a normal condition so that these inhibiting factors cannot be guaranteed to disappear. In addition, the supporting factor is organizational leadership ensuring that the vision and mission of the regional head as stated in the RPJMD in the Department of Women's Empowerment, Child Protection, Population Control and Family Planning in Bintan Regency, which gets special attention as stated in the mission of the Regent of Bintan Regency 2021-2026.